An in vitro analysis of separation of multi‐use ProTaper Universal and ProTaper Next instruments in extracted mandibular molar teeth. Issue 4 (27th March 2015) - Ertas, Huseyin; Capar, Ismail Davut
Summary This study investigated the separation incidence of reused ProTaper Universal and ProTaper Next rotary instruments and identified the location of separated fragments. The root canals of extracted human mandibular molars were prepared with 10 assorted sets of ProTaper Universal and ProTaper Next instruments. After each preparation, instrument sets were autoclaved. This arrangement was repeated until an instrument fractured. The number of prepared teeth until fracture occurred was recorded for each instrument set. Teeth in which the instruments fractured were analyzed to determine the separation grade, apical relation, and coronal position. Fracture surfaces of the instruments were examined with scanning electron microscope. ProTaper Universal instruments fractured after application to a mean of 7.3 teeth, and ProTaper Next instruments after application to a mean of 5.7 teeth (p > 0.05). In the ProTaper Universal and ProTaper Next groups, F2 and X1 were the most commonly fractured instruments, respectively. Torsional and cyclic failures were evenly distributed in both the groups. The mean lengths of the fractured fragments of the instruments showed no statistically significant difference. The distance between the tip of the fractured instruments and apical constriction was similar (p > 0.05). However, the mean distance between the root canal orifice and coronal part of the fractured instrument was shorter in the ProTaper Next group (p < 0.05). The life span of ProTaper Universal and ProTaper Next instruments was the same for preparation of mandibular molar teeth. None of the instruments were fractured in the first usage. SCANNING 37:270–276, 2015. © 2015 Wiley Periodicals, Inc.